1993
DOI: 10.1038/366687a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of a metabotropic glutamate receptor in synaptic modulation in the accessory olfactory bulb

Abstract: Various functions of glutamate transmission are mediated by both ionotropic and metabotropic glutamate receptors. The metabotropic glutamate receptors (mGluRs) consists of at least six different subtypes that are classified into three subgroups, mGluR1/mGluR5, mGluR2/mGluR3, and mGluR4/mGluR6 (refs 1-5), but their physiological roles are largely unknown. Here we report the identification of a very potent agonist for mGluR2/mGluR3, DCG-IV, and the specific localization of mGluR2 in granule cell dendrites that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
214
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 343 publications
(231 citation statements)
references
References 21 publications
15
214
2
Order By: Relevance
“…DCG IV has been shown to inhibit forskolin-stimulated cyclic AMP formation with potencies of 300 and 200 nM for Chinese hamster ovary cells expressing mGlu2 and mGlu3 receptors, respectively (Hayashi et al, 1993), and these values fit well with the affinity found for both rat brain cortex and mGlu2-transfected membranes. DCG IV was also reported to inhibit NMDA receptors with an EC 50 close to 3 jiM (Hayashi et al, 1993). However, NMDA was unable to inhibit [ 3H] DCG IV binding, even at a high concentration.…”
Section: [3h]dcg IV Binding To Rat Brain Sectionssupporting
confidence: 63%
See 3 more Smart Citations
“…DCG IV has been shown to inhibit forskolin-stimulated cyclic AMP formation with potencies of 300 and 200 nM for Chinese hamster ovary cells expressing mGlu2 and mGlu3 receptors, respectively (Hayashi et al, 1993), and these values fit well with the affinity found for both rat brain cortex and mGlu2-transfected membranes. DCG IV was also reported to inhibit NMDA receptors with an EC 50 close to 3 jiM (Hayashi et al, 1993). However, NMDA was unable to inhibit [ 3H] DCG IV binding, even at a high concentration.…”
Section: [3h]dcg IV Binding To Rat Brain Sectionssupporting
confidence: 63%
“…It is interesting that the affinity constant determined by using the onesite model (180 nM) was extremely close to the value found for the mGlu2 receptor-transfected cell membranes~KD value of 160 nM (Cartmell et al, 1998)]. DCG IV has been shown to inhibit forskolin-stimulated cyclic AMP formation with potencies of 300 and 200 nM for Chinese hamster ovary cells expressing mGlu2 and mGlu3 receptors, respectively (Hayashi et al, 1993), and these values fit well with the affinity found for both rat brain cortex and mGlu2-transfected membranes. DCG IV was also reported to inhibit NMDA receptors with an EC 50 close to 3 jiM (Hayashi et al, 1993).…”
Section: [3h]dcg IV Binding To Rat Brain Sectionsmentioning
confidence: 92%
See 2 more Smart Citations
“…Albeit during the last 2 decades, progress in the knowledge of the VNS in general and of the AOB in particular has been considerable (Hayashi et al, 1993;Taniguchi and Kaba, 2001;Araneda and Firestein, 2006), there are still some specific aspects of the AOB that require further exploration. Among the issues in need of precision is the exact morphology of the AOB, especially when it is obtained from mice.…”
mentioning
confidence: 99%